DETERMINANTS OF EMPLOYEE PERFORMANCE ON JOB TRAINING, CAREER DEVELOPMENT AND ORGANIZATIONAL CULTURE - Eriyanti, Ganita Putri; S, Ira Puspitadewi; Murtalining, Wenny (Dynamic Management Journal, 2025)
Effective HR management is the key to organizational success, including in universities. This study analyzes the influence of job training, career development, and organizational culture on the performance of permanent employees of the University of Muhammadiyah Jember. The quantitative method was used by saturated sampling on 135 respondents through a questionnaire. Data were analyzed using multiple linear regression, hypothesis testing, and determination coefficients. The results showed that all three variables had a significant effect on performance (R² = 0.803 or 80%), proving that the development of human resources and a strong organizational culture increases productivity. These findings make a practical contribution to universities in designing more effective HR management strategies.